DANCE AS CULTURAL LEDGER: THE VALUE OF DOCUMENTING INDIGENOUS AFRICAN DANCES - Obeghare Izu, Benjamin Obeghare Izu1; de Villiers, Alethea (E-Journal of Cultural Studies, 2023)
This article explores the significance of documenting indigenous African dances, specifically focusing on the Umxhentso dance within the cultural context of Xhosa amagqirha in the Eastern Cape province of South Africa. Historically, Indigenous dances in African societies have served as crucial elements of communal ceremonies, embodying cultural traditions, spiritual beliefs, and social cohesion. However, colonialism and contemporary globalisation have threatened the preservation of these traditional dance forms. This paper employs a qualitative approach, incorporating interviews with participants and observations and extant literature and data analysis using thematic analysis. The findings underscore the multifaceted role of the Umxhentso dance, highlighting its function as a medium for connecting with ancestors, enhancing divination practices, and reinforcing spiritual potency within the community. Moreover, the article emphasises the value of documenting indigenous dances in combating stereotypes and misconceptions, preserving cultural heritage, and promoting intercultural understanding. This study contributes to the ongoing discourse on the importance of safeguarding and revitalising indigenous African dances to preserve cultural diversity and identity. Keywords: Umxhentso dance; Cultural heritage; documenting indigenous dances; African traditional dances; Xhosa culture; Indigenous dance.